A longitudinal study on perceived burdensomeness and its influencing factors among older adult hemodialysis patients who migrated with their families in China - Liu, Yun; Lv, Hailin; Sun, Ke; Gao, Zhaoli (Frontiers in Public Health, 2025)
ObjectiveThe perceived burdensomeness is a negative emotion and cognition that arises from an individual’s belief that they place an excessive burden on others. For older adult hemodialysis patients who migrated with their families, they not only endure the pain of their illness but also face the challenges of living in a different place. They worry that their illness will burden their families, and perceived burdensomeness may be even more pronounced. This study aimed to explore the trend of perceived burdensomeness over time and its influencing factors in older adult migrant hemodialysis patients in China.MethodsA longitudinal study was conducted on 120 older adult hemodialysis patients who migrated with their families in Qilu Hospital of Shandong University from June 2022 to October 2023. The patients were surveyed using the perceived burdensomeness subscale, general information questionnaire, and family support scale at T1 (first admission for hemodialysis), T2 (6 months after hemodialysis), and T3 (12 months after hemodialysis). Changes in perceived burdensomeness and family support were analyzed. Generalized estimating equations were used to analyze factors influencing perceived burdensomeness among older adult migrant hemodialysis patients.ResultsThis study initially included 120 older adult hemodialysis patients who migrated with their families as research subjects, and no patient dropped out during the study. Among them, 61 were male, with an average age of (71.9 ± 7.5) years. 86 were married, and 34 were divorced or widowed. 68 were able to take care of themselves, and 52 were unable to. 74 had one adult child, 36 had two adult children, and 10 had three or more adult children. The perceived burdensomeness scores of patients showed a gradually increasing trend across the three time points (T1: 23.29 ± 3.82, T2: 23.98 ± 3.84, and T3: 24.58 ± 3.84), remaining consistently at a high level. The family support scores showed a gradually decreasing trend (T1: 10.25 ± 1.91, T2: 9.70 ± 1.84, and T3: 9.13 ± 1.88). The differences in both perceived burden and family support scores across the three time points were statistically significant (F = 3.337, 10.702, all p < 0.05). Generalized estimating equation analysis revealed that marital status, household registration, family income per capita, number of adult children, self-care ability, comorbidities, dialysis frequency, and family support significantly influenced the changes of perceived burdensomeness among older adult migrant hemodialysis patients (P<0.05).ConclusionThe perceived burdensomeness of older adult migrant hemodialysis patients shows a trend of gradual increase over time and is at a relatively high level. Targeted intervention measures should be formulated according to the patients’ marital status, household registration, family income per capita, number of adult children, self-care ability, comorbidities, dialysis frequency and family support to improve the patients’ perceived burdensomeness, mental health level and quality of life.